Relations between language and cognition in native‐signing children with autism spectrum disorder. Issue 12 (3rd March 2016) - Shield, Aaron; Pyers, Jennie; Martin, Amber; Tager‐Flusberg, Helen
Abstract : Two populations have been found to exhibit delays in theory of mind (ToM): deaf children of hearing parents and children with autism spectrum disorder (ASD). Deaf children exposed to sign from birth by their deaf parents, however, show no such delay, suggesting that early language exposure is key to ToM development. Sign languages also present frequent opportunities with visual perspective‐taking (VPT), leading to the question of whether sign exposure could benefit children with ASD. We present the first study of children with ASD exposed to sign from birth by their deaf parents. Seventeen native‐signing children with a confirmed ASD diagnosis and a chronological‐ and mental age‐matched control group of 18 typically developing (TD) native‐signing deaf children were tested on American Sign Language (ASL) comprehension, two minimally verbal social cognition tasks (ToM and VPT), and one spatial cognition task (mental rotation). The TD children outperformed the children with ASD on ASL comprehension ( p < 0.0001), ToM ( p = 0.02), and VPT ( p < 0.01), but not mental rotation ( p = 0.12). Language strongly correlated with ToM ( p < 0.01) and VPT ( p < 0.001), but not mental rotation ( p = ns ). Native exposure to sign is thus insufficient to overcome the language and social impairments implicated in ASD. Contrary to the hypothesis that sign could provide a scaffold for ToM skills, we find that signing children with ASD are unable to access language so as to gain any potential benefit sign might confer. Our results support a strong link between the development of social cognition and language, regardless of modality, for TD and ASD children. Autism Res 2016, 9: 1304–1315 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.